Basic cell biology - Lesley H. Greene; Gilbert Shama (2012)
There is no simple answer to the question ‘what is life?’ The question is itself open to all sorts of interpretations that range from the strictly biochemical to the profoundly philosophical. Although the attributes of a living organism may at one level appear intuitive, they are actually very difficult to set down with economy in such a way as to encompass all known life forms. Paradoxically, it might be those engaged in the search for extra-terrestrial life who, not being bound to what might just turn out to be terrestrial adaptations, succeed in arriving at a truly universal definition of life. Returning to Earth, we must always guard against accepting the commonly observed as being definitive: just last year a bacterium was isolated from a lake in California in which the phosphorus present in its DNA could be substituted for by arsenic (Wolfe-Simon et al., 2010). We are therefore obliged to proceed without the luxury of a crisp definition of life, but that need not impede our objectives here which are of a strictly utilitarian purpose; to provide our readers – who we assume are engineers and physical scientists – with an appreciation of the nature of living organisms. These engineers and scientists share at least one thing in common – an interest in the interaction of atmospheric gas plasmas with living organisms, and although this puts in to context our objectives, we will only have cause to mention gas plasmas at the very end of this chapter. In attempting to meet our objectives we are mindful of the limitations imposed upon us; we have but one chapter in which to convey what the essence of living organisms is.